PEMENUHAN KEBUTUHAN PSIKOLOGIS PESERTA DIDIK SD/MI MELALUI PEMBELAJARAN TEMATIK-TERPADU - Andi Prastowo (Universitas Ahmad Dahlan, 2014)
One of thebiggest education problematika in Indonesia is lowering of quality of education of base in elementary school which is very determine to next education continuation. Real government havestrived various policy to overcome the mentioned, proven but not yet yielded repair which is significant. Seen from perception in field, the problem of low quality of this education seems more because factorquality of study process which a long way off from psychological requirement of student. But, specified of Curriculum 2013 commending to every teacher in elementary school to be using approach of integrated learning is smart breakthrough because in harmony with characteristic think student which still operational of concrete and holistik.